The other side of truth - Naidoo, Beverley. (HarperCollins, 2001)
Smuggled out of Nigeria after their mother's murder, Sade and her younger brother are abandoned in London when their uncle fails to meet them at the airport and they are fearful of their new surroundings and of what may have happened to their journalist father back in Nigeria.